2016
DOI: 10.1002/14651858.cd006982.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Cycled light in the intensive care unit for preterm and low birth weight infants

Abstract: Trials assessing the effects of CL have enrolled 544 infants. No study reported on our primary outcome of weight at three or six months. Results from one additional study strengthen our findings that CL versus CBL shortens length of stay, as does CL versus ND. The quality of the evidence on both comparisons for this outcome according to GRADE was low. Future research should focus on comparing CL versus ND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 59 publications
0
20
0
1
Order By: Relevance
“…Evidence on several clinically important topics includes no RCTs sponsored by industry. Topics such as assessing head elevation for severe brain injury [ 36 ], music to calm mechanically ventilated patients [ 37 ], cycled lights in neonatal intensive care units [ 38 ], or cough augmentation techniques for extubation [ 39 ] are procedures where the lack of industry funding is easily explained. Such procedures do not necessarily involve equipment or products manufactured by the biopharmaceutical, biotechnology, or other health-related industry.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on several clinically important topics includes no RCTs sponsored by industry. Topics such as assessing head elevation for severe brain injury [ 36 ], music to calm mechanically ventilated patients [ 37 ], cycled lights in neonatal intensive care units [ 38 ], or cough augmentation techniques for extubation [ 39 ] are procedures where the lack of industry funding is easily explained. Such procedures do not necessarily involve equipment or products manufactured by the biopharmaceutical, biotechnology, or other health-related industry.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it should be perhaps no surprise that several studies on preterm infants revealed that imposing a rhythm to the NICU lighting conditions exerts beneficial acute effects, e.g. faster weight gain and recovery, shorter hospitalization [91][92][93][94][95]. Some benefits were found to be stronger than others, but all were encouraging.…”
Section: Neonatal Units and White Matter Injurymentioning
confidence: 97%
“…Introducing a robust light-dark cycle in the NICU has been suggested as a strategy to entrain the circadian system in preterm infants, which may support growth and development as well as help prevent complications frequently experienced by the preterm infant such as disturbances in body temperature, sleep or feeding patterns ( Morag and Ohlsson, 2016 ). Currently, lighting conditions in NICUs across the world are highly variable, owing to flexible guidelines (e.g., see Best et al, 2018 ).…”
Section: Circadian Entrainment By Light-dark Cycles In the Neonatal Imentioning
confidence: 99%
“…For example, the Consensus Committee for NICU Design, recommends illuminance levels to be between 10 and 600 lux in the NICU ( White et al, 2013 ). NICUs can be distinguished by observing either constant light or constant near-darkness, with light levels below 20 lux throughout the 24-h period ( Morag and Ohlsson, 2016 ).…”
Section: Circadian Entrainment By Light-dark Cycles In the Neonatal Imentioning
confidence: 99%
See 1 more Smart Citation